Frontispiece: Efficient Asymmetric Biomimetic Aldol Reaction of Glycinates and Trifluoromethyl Ketones by Carbonyl Catalysis. Issue 37 (30th August 2021) - Cheng, Aolin; Zhang, Liangliang; Zhou, Qinghai; Liu, Tao; Cao, Jing; Zhao, Guoqing; Zhang, Kun; Song, Guanshui; Zhao, Baoguo
Abstract : Organocatalysis In their Communication on page 20166, Guoqing Zhao, Baoguo Zhao et al. describe a highly efficient asymmetric biomimetic aldol reaction of glycinates and trifluoromethyl ketones via carbonyl catalysis.